Digital Messaging for Mathematical Understanding: A Systematic Review of Whatsapp Use in Indonesian Junior High Schools - Valeria Yekti Kwasaning Gusti; Khaola Rachma Adzima (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2026)
This study aims to investigate how WhatsApp has been used to deliver mathematics lessons in Indonesia across multiple educational levels, with a particular focus on junior high schools, within the last four years. The objective is to identify the extent, practices, and effectiveness of WhatsApp as either a primary or supplementary instructional tool in mathematics teaching at the elementary, junior high, senior high, and tertiary levels. The research method employed was a systematic literature review of Scopus-indexed journal articles published in English between 2019 and 2024. Relevant studies were selected, analyzed, and synthesized according to their research design, educational level, and findings. Both qualitative and quantitative research were included to provide a comprehensive understanding of how WhatsApp has been integrated into mathematics education. In many cases, WhatsApp is integrated into instructional designs such as blended learning, flipped classroom activities, and collaborative problem solving, allowing students to interact with teachers and peers. The results show that WhatsApp is widely adopted by Indonesian teachers, particularly during and after the pandemic, to facilitate communication, share learning materials, and support problem-solving activities. At the elementary and junior high levels, studies report that WhatsApp helps improve students’ motivation and engagement, though the impact on learning outcomes is mixed. At the senior high and vocational levels, WhatsApp is often combined with other digital platforms such as YouTube to support blended learning. Evidence from higher education remains limited, with indications that WhatsApp serves mainly as a communication channel rather than a structured learning platform. In conclusion, WhatsApp is a practical, low-cost, and accessible tool that supports mathematics instruction in Indonesia. However, its effectiveness depends on instructional design, teacher facilitation, and integration with other pedagogical strategies